REKAYASA APLIKASI CENTER RUMAH KOST BERBASIS WEB DI KABUPATEN SUMBAWA - Yuliadi Yuliadi; Nurul Maulida Solihat; Herfandi Herfandi (Jurnal Manajemen Informatika dan Sistem Informasi, 2021)
A boarding house is a temporary residence for living with a number of rooms that are rented out and paid for within a certain period of time. This study aims to build a boarding house center application in Sumbawa Regency as a means of providing effective housing information for boarding house seekers, tenants, and boarding house owners to promote boarding houses to be rented out. This application was developed using qualitative research and built using the PHP programming language using MySql as a database. The method used in building this application is using the waterfall method with UML (Unified Modeling Language) modeling. This application is expected to make it easier for boarding house seekers and boarding house owners to do promotions.